SeaChange Pre-Sales engineering functions, sales, processes, tools and techniques - Kwong, Jefferson R.; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, 2014)
SeaChange International is a global leader for technologies and services focused on transformative multi-screen video. The company collaborates with cable and telecom companies worldwide to deliver high-tech video experience that can be accessed anytime and anywhere on a multitude of viewing devices. At the same time, SeaChange works closely with its customers to bridge the gap between technology and business. This project covers Technology Management topics related to the establishment of a new engineering team within the SeaChange In-Home (SCIH) business unit aptly called "Pre-Sales Engineering." The four key deliverables of this project are : 1. Formally define the scope and function of SCIH's Pre-Sales Engineering team; 2. Formally definite the roles and responsibilities of a pre-sales engineer; 3. Identify and improve SCIH's Pre-Sales Demo Acceptance Process through the use of some process improvement methodology (i.e., Business Process Management or BPM); and 4. Identify tools and technologies so the Pre-Sales Engineering team can deliver its functions. After careful research and analysis, this project concludes that the SCIH Pre-Sales Engineering team should be able to gather and understand the business requirements of customers and provide technical solutions using SeaChange products. A SCIH pre-sales engineer has a primary role of leading technical consultancy and R&D tasks for demo and sales activities. As the go-to person and bridge between business and engineering, a pre-sales engineer should have the skills, knowledge, and qualities fit for dual roles. The pre-sales engineer should take the lead in coordinating demo activities for internal engineering, sales, management, customers, and third party vendors. Three high-level processes are highlighted for the demo support task executed in this order : demo acceptance process, demo setup process, and demo releases and deployment process. The application of Business Process Management enabled the analysis of the current demo acceptance process, which then led to its improvement. Some of the communication and customer relations tools and technologies that can be used include e-mail, phone, chat and conference calls, file storage, document synchronization, in-house host servers for storage and remote connections tools.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: SeaChange International; Pre-selling.; SeaChange